Comparing community-based reading interventions for middle school children with learning disabilities: possible order effects when emphasizing skills or reasoning - Archibald, Lisa M. D.; Davison, Christine; Kuiack, Alyssa; Doytchinova, Stella; King, Colin; Shore-Reid, Deborah; Cook, Paul; Vollebregt, Meghan (Frontiers in Education, 2023)
There is an abundance of community-based reading programs for school-age children who are struggling learners, including individuals with learning disabilities that include reading challenges. The aim of this study was to compare two community-based programs (i.e., skill and reason-based programs) and to analyze any complementary benefits. In this randomized cross-over study, 20 children completed two 8-week literacy intervention programs. The skills-based program, Leap to Literacy, focused on explicit teaching and repeated practice of the five key components of literacy instruction (phonemic awareness, phonics, fluency, vocabulary, comprehension). The reason-based program, Wise Words, focused on morphological knowledge, hypothesis testing, and critical thinking. Results revealed study-wide improvements in phonemic awareness, nonword reading, passage reading accuracy, spelling words and features, and affix identification. There were consistent program by program order effects with robust effects of completing the skills-based program first for phonemic awareness, the reason-based program first for passage reading accuracy, and both programs for affix identification. A significant increase in an oral language measure, recalling sentences, was observed for the group who completed the reason-based program first, although they also started off with a lower initial score. Findings indicated improvements from participating in either program. The observed order effects suggest potential additive effects of combining reasonand skills-based approaches to intervention.